Microwave Ablation of Spinal Osteoid Osteoma—Role of Air Insulation - Yadav, Ajit; Seth, Raghav; Gupta, Arun (Journal of Clinical Interventional Radiology ISVIR, 2022)
Osteoid osteomas are benign tumors seen in children and young adults. The management options include surgical resection and percutaneous ablation. In the present scenario, percutaneous ablation is the preferred modality, as it is minimally invasive, safe, and reliable. However, when the tumor is near a heat-vulnerable structure, thermal injury can occur.We report the case of spinal osteoid osteoma in a young female that was treated by microwave ablation (MWA) with air insulation to prevent heat injury to the spinal cord. Currently, there is paucity of literature describing the use of air insulation with MWA. In this report, we describe the technique, advantages, and limitations of using air insulation with MWA.
Keywords: osteoid osteoma; microwave ablation; air insulation